Plant diversity in Hazarikhil Wildlife Sanctuary of Chittagong and its conservation management - Rahman, MA (Journal of Biodiversity Conservation and Bioresource Management, 2018)
Plant diversity inventory in the Hazarikhil Wildlife Sanctuary of Bangladesh has been made through qualitative survey and their status of occurrence assessed for taking proper conservation management. The inventory has recognized 89 dicot (Magnoliopsida) families represented in this wildlife sanctuary by 305 genera and 478 species with in an area of 2908.5 ha. Of these, 86 (18%) species were assessed to be rare and endangered while 14 (2.93%) critically endangered. Determination of habit type resulted 189 (39.54%) species of trees, 119 (24.90%) shrubs including 26 (5.44%) climbers and 170 (35.56%) herbs including 46 climbers and two epiphytes. Three species, thought to be possibly extinct from the flora of Bangladesh, are being reported as rediscovery from this sanctuary, these are: Aglaia edulis (Roxb.) Wall., Knema erratica (Hook.f. and Thom.) J. Sinclair and Artabotrys caudatus Wall ex Hook.f. and Thom. An enumeration of these taxa is prepared citing each species with family name, bangla/local name(s), habit and conservation status for supporting the preparation of protected area management plan for implementation of National Conservation Strategy. J. Biodivers. Conserv. Bioresour. Manag. 2017, 3(2): 43-56